Avaliação de diferentes inclinações e exposições de telhado em três tipos de cobertura em modelos reduzidos de instalações zootécnicas - Melo, Thiago; Furlan, Renato [UNESP]; Milani, Adhemar [UNESP]; Buzanskas, Marcos [UNESP]; Moura, Adolpho; Mota, Diego; Cardoso, Diercles [UNESP] (Universidade Estadual de Londrina, 2013)
The present study was developed in Departamentos de Engenharia Rural e Morfologia e Fisiologia Animal da FCAV/Unesp. The objective of evaluating different roof slopes and exposure in three types of coverage in models of animal installations. Project 48 built reduced models of wood were used with dimensions of 1,00 x 1,00 x 0,50 meters. The covering was one water, lateral and wood floor, disposed in the exhibitions North-south, being 24 prototypes in the north exhibition and 24 in the south. Were used in the covering roofs of ceramic type, galvanized steel and asbestos. The slopes varied of 20, 30, 40 and 50% for ceramic tile and 10, 30, 40 and 50% for the others and with two repetitions for slope. Inside the reduced models temperature readings were accomplished, of hour in hour during one year, for the system of acquisition of Data Logger Campbell Scientific-Ínc and externally the temperature of the air, incident radiation global solar, precipitation, speed and relative humidity of the air were measured. The results obtained during the experimental period of one year were appraised statistically for the statistical package SAS in the factorial outline, where three factors were considered: tile type, slope degree and exposure. The obtained averages were compared through the test of Tukey to 5% of probability. After analyzing the data we found that with increasing slope, there was a decrease in inside temperature in the cover prototypes, therefore, using steeper slopes with 50% of tipping ceramics and asbestos, with greater coverage on display South, we have lower temperatures in poultry houses in the geographic coordinates of the city of Jaboticabal.
Evaluation of different roof slopes and exposure in three types of coverage in models of animal installations
Keywords: Environment; Poultry; Poultry house; Temperature